Genetic surveillance and the emergence of SARS-CoV-2 variants - Thomson, Emma (Henry Stewart Talks, 2021)
Identification of a range of SARS-CoV-2 variants and their associated mutations, Genetic surveillance of SARS-CoV-2 across the world, Most worrying variants currently in circulation, Potential emergence of novel variants combining multiple mutations within a single viral genome, Comparison of the rate of mutation of SARS-CoV-2 with that of other seasonal coronaviruses and the flu